Combination of bicarbonate and low temperature stress induces the biosynthesis of both arachidonic and docosahexaenoic acids in alkaliphilic microalgae Dunaliella salina HTBS - Guo, Zhile; Hou, Yuyong; Liu, Zhiyong; Ma, Yanbo; Han, Tong; Hao, Nahui; Yao, Yuanjiang; Lan, Chunxuan; Ge, Tongling; Safavi, Maliheh; Wang, Weijie; Zhao, Lei; et al. (Frontiers in Marine Science, 2022)
High bicarbonate levels and low temperature may have an impact on microalgae cultivation. However, changes in cellular composition in response to the combination of the above stresses are still poorly understood. In this study, the combined effects of bicarbonate and low temperature on biochemical changes in alkaliphilic microalgae Dunaliella salina HTBS were investigated. Comparing to the control condition of 25 oC without bicarbonate, the cell density was increased from 0.69 to 1.18 in the treatment condition of 0.15 M bicarbonate and low temperature (16 oC) while the lipidcontents were increased from 34.71% to 43.94%, 22.44% to 26.03%, 22.62% to 29.18%, respectively. Meanwhile, the PUFAs, arachidonic acid (AA) and docosahexaenoic acid (DHA) contents reached to 3.52% and 4.73% with the combination of low temperature and bicarbonate, respectively, whereas they were not detected when the cells were treated with single condition. Moreover, both the chlorophyll and carotenoid contents were also detected with increased profiles in the combined treatments. As a result, the maximum photochemical efficiency but not reduced non-photochemical quenching was strengthened, which enhanced the photosynthetic performance. Additionally, our results indicated that D. salina HTBS could acclimate to the combined stress by up-regulating the activity of SODand reducing MDA content. These findings demonstrated that the addition of a certain bicarbonate under low temperature could effectively enhance the biomass production and accumulation of AA and DHA, which would benefit the development of the microalgae industry in value-added products.